2015
DOI: 10.1016/j.actamat.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal annealing of shocked zirconium: Stability of the two-phase α/ω microstructure

Abstract: Under high pressure conditions, Zr undergoes a phase transformation from its ambient equilibrium hexagonal close packed α phase to hexagonal ω phase. Upon returning to ambient conditions, the material displays hysteretic behavior, retaining a significant amount of metastable ω phase. This study presents an in-situ synchrotron X-ray diffraction analysis of Zr samples shock-loaded to compressive peak stresses of 8 and 10.5 GPa and then annealed at temperatures of 443, 463, 483, and 503K. The evolution of the α p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…α/ω interface, dislocations, grain boundaries, etc.). The molecular dynamics study of Zong suggested that the reverse transformation via interfacial growth of existing martensitic α laths was less likely to occur than the defect mediated heterogenous nucleation process at all temperatures, which was inconsistent with the ex-situ annealing experiments from Low et al [25]. This apparent disagreement between molecular dynamics predictions and experimental observation indicates that a more detailed description of the defect states and their role in the reverse transformation is warranted.…”
Section: Prior Modeling and Simulationmentioning
confidence: 89%
See 4 more Smart Citations
“…α/ω interface, dislocations, grain boundaries, etc.). The molecular dynamics study of Zong suggested that the reverse transformation via interfacial growth of existing martensitic α laths was less likely to occur than the defect mediated heterogenous nucleation process at all temperatures, which was inconsistent with the ex-situ annealing experiments from Low et al [25]. This apparent disagreement between molecular dynamics predictions and experimental observation indicates that a more detailed description of the defect states and their role in the reverse transformation is warranted.…”
Section: Prior Modeling and Simulationmentioning
confidence: 89%
“…The data used to develop and validate this model came from annealing studies of shocked Zr performed by Low et al [25] and Brown et al [24]. The shocked material for those studies came from gas gun experiments performed by Ceretta and collaborators [4,6,9,26,27].…”
Section: Production Of Metastable ω Through Shock Impactmentioning
confidence: 99%
See 3 more Smart Citations